TIPE2 (Tumor Necrosis Factor α-induced Protein 8-like 2) Is a Novel Negative Regulator of TAK1 Signal - Oho, Michitaka (J Biol Chem, 2016)
TIPE2 (TNF-α-induced protein 8-like 2) is a novel death effector domain protein and is a negative regulator of the innate and adaptive immune response. Although it has been demonstrated that caspase-8 contributes to the negative regulation of TIPE2, the negative regulatory mechanism is not entirely understood. Here, we demonstrate that TIPE2 interacts with TGF-β-activated kinase 1 (TAK1), a crucial regulatory molecule of inflammatory and immune signals, and consequently acts as a powerful negative regulator of TAK1. The interaction between endogenous TIPE2 and TAK1 was observed in RAW264.7 macrophage-like cells and mouse primary cells derived from spleen and thymus. The TIPE2 amino acid 101–140 region interacted with TAK1 by binding to the amino acid 200–291 region of the internal kinase domain of TAK1. TIPE2 interfered with the formation of the TAK1-TAB1-TAB2 complex and subsequently inhibited activation of TAK1 and its downstream molecules. Importantly, silencing TIPE2 through RNA interference attenuated the inhibitory action of TIPE2 on LPS- and TNF-α-stimulated TAK1 activity. Exogenous TIPE2 101–140, the region that interacts with TAK1, also inhibited LPS- and TNF-α-stimulated NF-κB reporter activity. Interestingly, cell-permeable TIPE2 protein maintained its binding ability with TAK1 and exhibited the same inhibitory action of native TIPE2 on TLR4 signaling in vitro. Thus, cell-permeable TIPE2 protein is a potential candidate for intracellular protein therapy for TAK1-related diseases. The present study demonstrates that TIPE2 acts as a novel negative regulator of inflammatory and immune responses through TAK1 signaling.